Relationship between external debt and economic growth: panel data analysis for BRIC countries (Journal of Economic Research & Business Administration, 2022)
The BRIC countries are the four largest emerging economies, accounting for a quarter of the world’stotal GDP. The external debt stock of the BRIC countries (3938 billion USD) corresponds to 46.22% ofthe total foreign debt stock of the developing countries (8520 billion USD). The role of foreign debt inthe economic development of a country is one of the most discussed and interesting topics in macroeconomicsamong researchers and politicians. Therefore, in this study, the relationship between foreign borrowingand economic growth in BRIC countries was examined. The data set used in the study belongsto the years 1990-2021 and panel cointegration method was used. As a result of the Westerlund (2007)panel cointegration test applied, a long-term relationship was found between foreign borrowing andeconomic growth variables in BRIC countries. The long-run cointegration vector was estimated with thepanel FMOLS estimator. According to our results; The long-run regression coefficient between externaldebt and economic growth in BRIC countries is -0.1108. This means that when the external debt stockin these countries increases by 1%, economic growth decreases by 0.11%. When evaluated on the basisof countries, the relationship between foreign debt and economic growth is positive for China, while therelationship is negative for Brazil, Russia and India.Key words: BRIC, External debt, economic growth, panel data analysis